The multi-visit-multi-voyage scheduling of the heterogeneous shuttle tanker fleet via inventory-oriented joint planning. (15th March 2023) - Li, Hao; Huang, Wentao; Li, Ran; Yu, Moduo; Tai, Nengling; Zhou, Songli
Highlights: This paper firstly considers the route scheduling of the shuttle tankers for the continuous production scenario. A novel multi-visit-multi-voyage model is formulated that enables the shuttle tankers to conduct the inventory-dependent route scheduling. The routing related variables are constructed in a reduced dimension to narrow the searching space for the solver. Abstract: The deep-sea oil exploitation leads to the growing utilization of the Floating Production Storage and Offloading (FPSO), where the crude oil is processed and stored until it can be transferred to a shuttle tanker. The conventional scheduling method of one shuttle tanker serving a fixed FPSO is challenged by the increasing numbers and capacities of the deep-sea FPSOs. This paper proposes a collaborative scheduling method by pooling the transportation capabilities of the shuttle tankers and conducting inventory-dependent route planning. The inventory headroom of the FPSO is taken as a key variable for the route planning of the shuttle tankers. A multi-visit-multi-voyage model is constructed to schedule the optimal routes for the shuttle tanker fleet in the multi-voyage time period. Case studies demonstrated that by implementing the collaborative scheduling, the proposed model could achieve 11.14% transportation cost saving in the planning period when compared with the conventional shuttle tanker scheduling model. By proper combining the shuttle tanker types, further cost savings can be obtained while using less shuttle tankers to execute oil transportation.